(untitled) (International journal of artificial intelligence, 2024)
Nowadays, technology has a huge role in modern education and in the modern world and nothing can be achieved without it. In addition, due to the development of business and marketing technologies in modern education, online learning is possible, namely Google, Zoom and You tube and a number of other sites and applications where you can learn. This is followed by a number of researches and articles, and based on these, we can say how to strengthen education, create a special approach to weak areas and students. (Soki D. Shyamlee, 2017)